Successive bilateral breast cancer - Borges, Freddy; Favat, Juan; Ramos, Sergio; Mate, Miguel; Priario, Julio (Cirugía del Uruguay, 1975)
A total of 921 breast cancers were studied in the "Hospital de Clínicas" during a 20-year period, since 1953 until 1973. The incidence found far the simultaneous bilateral breast- cancer was 0,65 %, while the incidence for the successive bilateral cancer was 1,3 %. Histopathologic studies showed that in most cases tumors in both breasts were different from each other. The second tumor occurred on the average 12 months after treatment of the first, and they generally arrived at the hospital in a more advanced evolutive stage. Based upon these data, behaviour to be observed concerning the remnant breast after radical mastectomy is analyzed, and it is found that prophylactic contralateral mastectomy is not justified.